Efficacy and safety of anamorelin in patients with cancer cachexia: Post‐hoc subgroup analyses of a placebo‐controlled study. (16th November 2022) - Takayama, Koichi; Takiguchi, Toru; Komura, Naoyuki; Naito, Tateaki
Abstract: Background: Cachexia, a disorder associated with anorexia, inflammation, and muscle wasting, is frequent in cancer patients. We performed post‐hoc analyses of the ONO‐7643‐04 study to investigate the efficacy and safety of anamorelin in subgroups of Japanese patients with non‐small cell lung cancer (NSCLC). Methods: The patients were divided into subgroups by baseline characteristics, including sex, age, body mass index, prior weight loss, performance status (PS), concomitant anticancer therapy, and number of previous chemotherapy regimens. The changes from baseline through to 12 weeks for lean body mass (LBM), body weight, and appetite were calculated. Appetite was evaluated using the quality of life questionnaire for cancer patients treated with anticancer drugs (QOL‐ACD) item 8 score. Responder rates were defined as the maintenance/improvement of LBM (≥0 kg), body weight (≥0 kg), or QOL‐ACD item 8 score (≥0) from baseline to all evaluation time points. Safety was evaluated in patients subgrouped by age and PS. Results: Anamorelin resulted in greater improvements versus placebo in LBM, body weight, and appetite in most subgroups. Anamorelin was also associated with greater LBM, body weight, and appetite responder rates than placebo in nearly all subgroups. Among anamorelin‐treated patients, adverse drug reactions (ADRs) tended to be more frequent with increasing age (<65 years, 19.2%; ≥65 to <75 years, 45.9%; ≥75 years, 60.0%) and PS score (PS 0–1, 38.4%; PS 2, 60.0%). The frequency of serious ADRs was 2.7% and 0% in the PS 0–1 and PS 2 subgroups, respectively. Conclusion: This study of NSCLC patients with cancer cachexia revealed consistent improvements in LBM, body weight, and appetite across most subgroups of anamorelin‐treated patients. This study also demonstrated the tolerability of anamorelin regardless of age and PS, with a low incidence of serious ADRs in each subgroup. Abstract : We performed post‐hoc analyses of the ONO‐7643‐04 study to investigate the efficacy and safety of anamorelin in subgroups of Japanese patients with non‐small cell lung cancer. This study revealed consistent improvements in lean body mass, body weight, and appetite score using QOL‐ACD item 8 across most subgroups of anamorelin‐treated patients versus placebo. This study also demonstrated the tolerability of anamorelin regardless of age and performance status, with a low incidence of serious adverse drug reactions in each subgroup.